Ego States Among a Sample of General Secondary School Teachers: A Field Study in the City of Masyaf (Journal of Hama University, 2026)
The current study aimed to identify the most common ego states among a sample of secondary school teachers in Masyaf city, as well as to examine differences in Egp states based on gender and years of teaching experience. The researcher utilized an ego state questionnaire designed by Claudia (2017), which was administered to a sample of 50 male and female teachers in Masyaf secondary schools after verifying its psychometric properties and suitability for application. The results revealed that the most prevalent ego state among the sample was the Adult ego state. Furthermore, the findings showed no statistically significant differences in the use or manifestation of ego states based on gender. However, statistically significant differences were found in the manifestation of the Adult ego state according to years of teaching experience, favoring teachers with more than 5 years of experience. No significant differences were found for either the Parent or Child ego states based on this variable
Keywords: EGO States; secondary school teachers; Masyaf City